Depression: an inflammatory illness?. Issue 5 (15th March 2012) - Krishnadas, Rajeev; Cavanagh, Jonathan
Abstract : Major depressive disorder (MDD) is associated with significant morbidity and mortality. Findings from preclinical and clinical studies suggest that psychiatric illnesses, particularly MDD, are associated with inflammatory processes. While it is unlikely that MDD is a primary 'inflammatory' disorder, there is now evidence to suggest that inflammation may play a subtle role in the pathophysiology of MDD. Most of the evidence that links inflammation to MDD comes from three observations: (a) one-third of those with major depression show elevated peripheral inflammatory biomarkers, even in the absence of a medical illness; (b) inflammatory illnesses are associated with greater rates of MDD; and (c) patients treated with cytokines are at greater risk of developing major depressive illness. We now know that the brain is not an immune privileged organ. Inflammatory mediators have been found to affect various substrates thought to be important in the aetiopathogenesis of MDD, including altered monoamine and glutamate neurotransmission, glucocorticoid receptor resistance and adult hippocampal neurogenesis. At a higher level, inflammation is thought to affect brain signalling patterns, cognition and the production of a constellation of symptoms, termed 'sickness behaviour'. Inflammation may therefore play a role in the aetiology of depression, at least in a 'cohort' of vulnerable individuals. Inflammation may not only act as a precipitating factor that pushes a person into depression but also a perpetuating factor that may pose an obstacle to recovery. More importantly, inflammatory markers may aid in the diagnosis and prediction of treatment response, leading to the possibility of tailored treatments, thereby allowing stratification of what remains a heterogenous disorder.